Primary Angiitis of the Central Nervous System in Adults: A Comprehensive Review of 76 Biopsy-Proven Case Reports - Lu P; Cui L; Zhang X (Dove Medical Press, 2023)
Ping Lu,1 Lingyun Cui,1 Xinghu Zhang2 1Center for Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, 100070, People's Republic of China; 2Department of Neuroinfection and Neuroimmunology, Center for Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, 100070, People's Republic of ChinaCorrespondence: Xinghu Zhang, Department of Neuroinfection and Neuroimmunology, Center for Neurology, Beijing Tiantan Hospital, Capital Medical University, No. 119, South Fourth Ring Road West, Beijing, 100070, People's Republic of China, Tel + 86 10 5997 6585, Email xhzhtiantan@hotmail.comPurpose: Primary angiitis of the adult central nervous system (PACNS) is an increasingly recognized but limited disease. Using previous case reports, we sought to summarize the clinical symptoms, imaging manifestations, treatment, and prognosis of patients with biopsy-confirmed PACNS to guide clinical diagnosis and management.Methods: We searched the Web of Science database for studies published from January 2000 to April 2023, with the language set to English and the document type limited to [Article or Review or Letter or Editorial Material]. A systematic review of all case reports met the inclusion and exclusion criteria was performed. These patients' clinical, pathological, and imaging characteristics were analyzed, and treatment and prognostic data were summarized.Results: We analyzed 69 articles, including 76 patients with biopsy-confirmed PACNS. And 57.9% of the patients were male, the median age at presentation was 47.0 years, and focal neurological deficits were the most common symptom in patients (78.9%), followed by headache (52.6%). The median duration of biopsy was 1.1 months, of which 49 (64.5%) patients were lymphocytic, 13 (17.1%) were granulomatous, 11 (14.5%) were amyloidotic, and 3 (3.9%) were necrotizing PACNS. Relapse events occurred in 41 (53.9%) patients, including 34 (44.2%) relapses and 8 (10.5%) deaths. Univariate logistic regression analysis revealed that symptomatic epilepsy, prolonged biopsy time window, and CD20 expression in pathological tissues might be independent risk factors for recurrent events in patients (HR=4.69, 95% CI: 1.51- 14.54, p=0.007; HR=1.11, 95% CI: 1.00- 1.22, p=0.043; HR=5.33, 95% CI: 1.07- 26.61, p=0.041).Conclusion: Adult PACNS is associated with frequent relapses and high mortality. Symptomatic epilepsy, prolonged biopsy time window, and CD20 expression in pathological tissue may be associated with recurrent events.Keywords: PACNS, biopsy, recurrence, CD20, comprehensive review